(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This article is about language policy and language planning and some issues that some writers came across the challenges in drawing up a plan, formulating language policy, and implementing and assessing it. LPP is a try by an agent or agents, mainly not at the governmental level (a macro level) to affect an individual’s or certain group’s future language attitudes (a micro level). In LPP, an issue is identified that needs to be solved by people who are designing and implementing a policy. If people targeted by the policy do not share the same perception of the issue, they may oppose its implementation by either doing so themselves or by changing it to suit their own interests or desires.